Solubility Enhancement by Solid Dispersion Method: An Overview - Vaishnavi Jadhav,; Pooja Kashid,; Kishor Otari,; Mohini Yadav, (Asian Journal of Pharmaceutical Research and Development, 2024)
To improve dissolution of poorly water-soluble drugs and thus enhancing their bioavailability, the dispersion of one or moreactive pharmaceutical ingredient in a carrier at solid state is used. This process is known as solid dispersion. It has engrossed significant interest as an efficient means of improving the dissolution rate. It happens due to dispersions of poorly water-soluble drugs with water-soluble carriers. The one of the most challenging aspects in formulation development is solubility behaviour of drugs. The number of poor water-soluble compounds has radically increased. Compared to conventional formulations such as tablets or capsules, solid dispersions prepared by various methods can be used which have many benefits over the above conventional dosage form. For the preparation of solid dispersions, few of the aspects are to be considered such as; selection of carrier and methods of physicochemical characterization. In this review, an emphasis is put on solubility, various types of solid dispersions, BCS classification, carriers, solid dispersion techniques, mechanism to enhance dissolution in solid dispersion, characterization, advantages, disadvantages and the application of the solid dispersions.